PRESS FREEDOM AND PREDICTABILITY OF STOCK MARKETS - PLEŞOIANU (TODEA), Anita (Studia Universitatis Babeș-Bolyai Oeconomica, 2015)
This study uses the Efficiency Index of Kristoufek and Vosvrda (2013) to investigate the relation between press freedom and the informational efficiency of 41 stock market indices over the period 1999 – 2012. We employ short memory (linear and nonlinear dependencies) and long memory as input variables for the Efficiency Index to control for different types of inefficiencies. Our panel results, supported by robustness tests, show a direct and significant relation between stock markets informational efficiency and press freedom. In addition, as expected, market capitalization and volatility are other two determinants of efficiency, whereas the degree of market openness has influence only on the long-term behavior of returns. JEL Classification: C13, G14, G15